2011
DOI: 10.1192/pb.bp.110.033241
|View full text |Cite
|
Sign up to set email alerts
|

Judgements about deprivation of liberty made by various professionals: comparison study

Abstract: Aims and methodA group of lawyers, psychiatrists, best interest assessors and independent mental capacity advocates were asked to make binary judgements about whether real-life situations in 12 vignettes amounted to deprivation of liberty. Kappa coefficients were calculated to describe the level of agreement within each professional group and for the total group of professionals.ResultsThere was total agreement between all professionals about deprivation of liberty in only 1 of the 12 cases. The overall level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 8 publications
1
23
0
Order By: Relevance
“…This is in opposition to much early discussion of DOLS, which tended to focus on the complexity of the system and confusion in professionals' minds (Cairns et al, 2011).…”
Section: Discussionmentioning
confidence: 95%
“…This is in opposition to much early discussion of DOLS, which tended to focus on the complexity of the system and confusion in professionals' minds (Cairns et al, 2011).…”
Section: Discussionmentioning
confidence: 95%
“…Perhaps, routine capacity assessments should be restricted to informal patients where there may be a deprivation of liberty? However, it has been shown that lawyers and clinicians are unreliable in assessing deprivation of liberty in informal patients without capacity [21,22], in part because the legal concept of deprivation of liberty is unclear, in contrast to mental capacity which is well-defined and reliably assessed in psychiatric inpatients [4]. The guidance suggests all informal patients should have capacity assessed at the start of admission, whether deprivation of liberty is at issue or not, and it seems hard for clinicians to avoid this obligation to ensure the best interests of their inpatients are served.…”
Section: Discussionmentioning
confidence: 99%
“…Cairns et al . (), however, found a less clear picture. The authors found that the overall level of agreement on what constituted a DOLS issue, between 23 professionals, about 12 vignettes, was only ‘slight’.…”
Section: Introductionmentioning
confidence: 89%
“…Although this finding is promising, the sample size (93) was small and self‐selecting (as with Cairns et al . ). In addition to this, there have been several developments arising from new case law and it is unclear how closely the authors connected their results with these revisions.…”
Section: Introductionmentioning
confidence: 97%